Search of Half Metallicity in VX (X = As, Sb and Bi) Compounds for Spintronic Applications - Singh, Hardev; Singh, Mukhtiyar; K. Kashyap, Manish (Asian Journal of Chemistry, 2011)
We present electronic and magnetic properties of VX (X = As, Sb and Bi) compounds in zinc blende structure by full potential linear augmented plane wave method using generalized gradient approximation as exchange correlation potential. Our calculations show that these compounds show robust half metallicity with the considerably half metallic gaps in minority spin channel and 100 % spin polarization at Fermi level EF. The total spin magnetic moment for both compounds is found to be 2.0 μB i.e. an integer value, which is in accordance with Slater- Pauling rule for governing half metallic compounds.